PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA PDAM TIRTA MOEDAL SEMARANG) - Darsita, 13.05.51.0101 (Students Journal of Economic and Management, 2017)
This study analyzes the influence of leadership style, work environment and job satisfaction on employee performance at PDAM Tirta Moedal Semarang. The population used in this research is the employees of PDAM Tirta Moedal Semarang and the number of samples in this study were 118 respondents. Data collection methods used in this study is using questionnaire (questionnaire) by distributing a list of questions to respondents to obtain information. The purpose of this study formulated to determine the influence of leadership style, work environment and job satisfaction on employee performance at PDAM Tirta Moedal Semarang. The analysis technique used is multiple regression analysis using SPSS19 program. The results of this research indicate that leadership style has a positive effect on employee performance, work environment and job satisfaction has no effect on employee performance. And jointly leadership style, work environment and job satisfaction affect the performance of employees. Keywords: leadership style, work environment, job satisfaction and employee performance